2015
DOI: 10.1155/2015/823829
|View full text |Cite
|
Sign up to set email alerts
|

In VitroInhibitory and Cytotoxic Activity of MFM 501, a Novel Codonopsinine Derivative, against Methicillin-ResistantStaphylococcus aureusClinical Isolates

Abstract: 28 new pyrrolidine types of compounds as analogues for natural polyhydroxy alkaloids of codonopsinine were evaluated for their anti-MRSA activity using MIC and MBC value determination assay against a panel of S. aureus isolates. One pyrrolidine compound, MFM 501, exhibited good inhibitory activity with MIC value of 15.6 to 31.3 μg/mL against 55 S. aureus isolates (43 MRSA and 12 MSSA isolates). The active compound also displayed MBC values between 250 and 500 μg/mL against 58 S. aureus isolates (45 MRSA and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
(46 reference statements)
4
12
0
Order By: Relevance
“…Results of this time-kill study corroborated with previous MBC/MIC ratio values [1] that suggested MFM501 has a bacteriostatic mechanism of action against MRSA and MSSA isolates.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Results of this time-kill study corroborated with previous MBC/MIC ratio values [1] that suggested MFM501 has a bacteriostatic mechanism of action against MRSA and MSSA isolates.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, by increasing its size, treated MRSA cells could also reduce their attachable surfaces against antibacterial compounds, hence, tolerating the stress conditions better than normal untreated cells [27]. This survival mechanism corroborated with earlier MBC/MIC ratio value of 32 for ATCC BAA-1688 against MFM501 [1]. Bacterial isolate that showed MBC/MIC ratio of ≥32 was considered tolerant or resistant towards the used anti-infective agent [1].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Nevertheless, upon changing the original reaction protocol to domino type reaction manner furnished the title compounds and their derivatives from moderate to excellent yields. This library of compounds was then subjected to antimicrobial study as part of our endeavor on the screening of biologically active heterocyclic type compounds [15][16][17][18].…”
Section: ■ Introductionmentioning
confidence: 99%